Dependence of the hindgut disappearance of phosphorus in pigs on the quantity of phosphorus entering the hindgut based on a Meta-analysis - Noa Park; Beob Gyun Kim (Animal Nutrition, 2025)
The objectives of the current study were to compare the difference between standardized ileal digestibility (SID) and standardized total tract digestibility (STTD) of phosphorus (P) in pigs using published data and investigate the factors that affect the hindgut disappearance of P in pigs. A total of 156 observations from 32 experiments that determined the apparent ileal digestibility and total tract digestibility of P in pigs were collected. The SID and STTD of P were calculated by accounting for basal endogenous losses of P. Standardized hindgut disappearance (SHD) of P was determined by subtracting the SID of P from the STTD of P. The Chi-square test was performed to investigate the association between SHD of P and categorical variables, including the use of phytase, the use of inorganic P sources, the use of corn-soybean meal-based diets, and body weight (BW) of pigs. To determine the effects of the SID of P on the SHD of P, a linear equation for the SHD of P was developed using the SID of P as an independent variable. The BW of pigs ranged from 10.0 to 104.8 kg and the SHD of P ranged from −22.8% to 39.8%. The STTD of P was greater than the SID of P (47.1% vs. 49.7%; P = 0.019). Based on the Chi-square analysis, the supplementation of inorganic P sources tended to result in a higher occurrence of a positive value for the SHD of P (P = 0.079). In addition, the occurrence of a positive value in the SHD of P was lower when the BW of pigs was below 30 kg. However, as the BW of pigs increased, the occurrence of a positive value in the SHD of P increased (P = 0.061). A regression analysis of the SHD of P against the SID of P in pigs indicated that the SHD of P decreased as the SID of P increased in pigs (r2 = 0.17; P < 0.001). In conclusion, the STTD of P is greater than the SID of P in pigs, and the SHD of P depends on the diet composition, the amount of P entering the large intestine, and the BW of the pigs.